PENGARUH DANA PIHAK KETIGA (DPK), PEMBIAYAAN BAGI HASIL, DAN FEE BASED INCOME TERHADAP PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA PERIODE 2014-2018 - Rafid Farhan Ramadhan; Alvien Nur Amalia (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to discuss and analyze Third Party Funds (DPK), Profit Sharing Finance and Fee Based Income. The data used in this study are secondary data from January 2014 - December 2018. This study uses the method of multiple linear regression analysis using the SPSS 24 computer program. The results of this study indicate that Third Party Funds (DPK), Profit Sharing Finance, and Fee Based Income simultaneously or jointly affect Profitability (ROA). Results on Fee Based Income affect partially to profitability (ROA), Third Party Funds are not affect partially to Profitability, profit sharing finance is not affect partially to Profitability (ROA).